Evaluation of the Doctrine of Marz-ul-Maut in Muslim Law: A Pakistani Perspective - Dr. Aatir Rizvi; Muhammad Azeem Farooqi (jihat-ul-islam, 2023)
In Islamic law there are rules and doctrines for almost every aspect of human life and property owned by a Muslim is at his disposal during his lifetime and even after his death, he has the freedom to make a will (upto a certain extent). The transfer of property during deathbed illness or Marz-ul-Maut is somewhat in between the transactions inter vivos and testamentary dispositions and here too, Muslim jurists have provided elaborated rules and principles. This article will briefly discuss different rules regarding transfers during marz-ul-maut and also the effects of this deathbed illness on other aspects of human life especially marriage, divorces and acknowledgment of debt etc during this illness. This article will discuss different laws, rules and principles applicable in Pakistan in the context of marz-ul-maut and also discuss the rules pertaining to different schools of thought. Further the principles being followed by courts in Pakistan in cases pertaining to issues involved with marz-ul-maut are also elaborated. The research is qualitative and doctrinal in nature.